Residual modulus degradation model for woven fabric composite determined by impulse excitation technique - Maciel, Maísa Milanez Ávila Dias [UNESP]; Shiino, Marcos Yutaka [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (Elsevier, 2020)
Structural components in the aircraft industries often require geometries that induce stress concentration effects, intensifying fatigue phenomena. When combined with a lack of structural monitoring it may limit composite applications. This research focuses on stiffness reduction of a notched carbon fiber laminate subjected to tension-tension fatigue load. The stiffness reduction was monitored during the cyclic tests by the use of the impulse excitation technique. Three major degradation stages were observed, the initial stage showed a high degradation rate followed by constant modulus degradation. The last stage was related to the presence of extensive delamination occurring outside of the notch area.
Keywords: 5HS woven; Carbon fiber; Crack propagation; Delamination; Epoxy